How to Apply the Accounting System in Financial Reporting for the Implementation of the Immediate Ngaben Ceremony in Puri Satria Kanginan, Klungkung-Bali - Ida Ayu Wiadnyani Manuaba (International Journal of Environmental, Sustainability, and Social Science (IJESSS), 2026)
This study aims to analyze the application of accounting systems in financial reporting for the Ngaben ceremony at Puri Satria Kanginan, Klungkung, Bali. The Ngaben ceremony, as a traditional activity involving collective funds, requires a transparent and accountable financial management and accountability mechanism. This study uses a qualitative descriptive approach with the interpretative phenomenological analysis (IPA) method. Data were obtained through interviews with the Sangkepan client, treasurer, and Serati section, supported by observation and documentation of financial reports. The results show that Puri Satria Kanginan has implemented a simple accounting system through systematic and documented recording of cash receipts and expenditures using Excel. Each activity section prepares an accountability report which is then summarized by the group treasurer into a final financial report. Although not fully referring to financial accounting standards (SAK), especially ISAK 35, this practice has reflected basic accounting principles such as recording, verifying transaction evidence, and transparency to group members. This study concludes that the application of an accounting system in the context of traditional ceremonies can improve accountability without eliminating the value of mutual cooperation and community traditions.